(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
This paper discusses a systematic approach to revising a second undergraduate course on microprocessor system design to improve student learning outcomes by introducing scripting-based design with a security mindset. The current course is based upon using the Dragon 12-Plus development system, which requires using compiled C code, and does not offer any on-board security features. The updated course has the intended outcomes of gaining design and technical skills on multiple microcontroller-based design platforms and introduce “security mindset” for networked systems. We introduce a Project Based Learning (PBL) approach, and the focus of the course is on hands-on activities where the students work on multiple design projects using C and MicroPython. The course hardware platform of Dragon 12-Plus is augmented with a small form factor pyboard, which is used to acquire sensor data and transmit securely for simple data analytics. We introduce three new laboratories, including one on data security using MicroPython. We also outline necessary changes to undergraduate engineering programming course sequence. Additionally, mapping of these new labs to CAE-CD KUs and the NICE Framework Specialty Areas is included.